Incorporating reflective writing into criminal justice courses. Issue 1 (2nd January 2020) - Scheidegger, Amie R.
ABSTRACT: Reflective writing is a transformative approach to understanding experiences, beliefs, and actions. By taking part in purposeful reflection, one should gain new understandings and appreciations for oneself and others. Reflection is a well established and essential component of lifelong learning and professional development.. If properly incorporated into one's thought process, reflection is a skill that can transcend the academic environment and spill over into career pathways and personal lives. This article provides the reader with an introduction to reflective writing, its many benefits to students, and why it should be incorporated into criminal justice courses. Examples of reflective writing assignments are provided to illustrate the variety of ways reflective writing can be utilized within a course to achieve desirable outcomes.